FORMATION OF ORTHOGRAPHIC AND ORFOEPIC CONCEPTS THROUGH PROVIDING PHONETIC KNOWLEDGE TO PRIMARY CLASS STUDENTS - Mamasidikova Naima Takhirjan kizi (Journals Park Publishing, 2024)
This article presents methods of forming orthographic and orthoepic knowledge of elementary school students by providing phonetic knowledge during their education. Using the knowledge acquired in the alphabet, mother tongue and reading literacy classes, creating a foundation for them to be able to perform tasks independently, the role of innovative technologies and exercises in achieving the intended results was discussed.
Keywords: Phonetics, phoneme, orthography, orthoepy, alliteration, pedagogical technology, speech, syllable, sound.